ANALISIS TRENDING TOPIC PADA BLOG SEPEDA MOTOR DI INDONESIA DENGAN MENGGUNAKAN TEXT PROCESSING STUDI KASUS IWANBANARAN.COM - Setiawan, Willy; Birowo, Sigit (Jurnal Informatika dan Bisnis, 2022)
This research was conducted because of the rapid flow of information that takes place along with the development of information and technology. Information technology was developed in order to facilitate and improve human performance in daily life. One form of  data that is widely used by us is text data. Text data is more difficult to process because of its unstructured form. Text processing is a part of data mining which consists of the process of extracting data in a very large number to retrieve important information and interesting patterns in it. In this study, text processing is done to obtain data on the patterns and the trends of data that often appears in a web. Data source obtained by the author from direct observation in the web page. Data taken consists of article title, posting date, tags, and link each article. The data collected together for further reprocessed using text processing and displayed through the Graphical User Interface display, better known by the term GUI for easily understood data by users. The result from this study is the tabular report that describes the trend of the discussion of each month from January to June, the trending topics for six months based on the number of documents and the total appearance, as well as the graphs showing the development trend of topics over time. Keywords: Analysis, Measurement, Blog, Tags, Text Processing, Tokenizing, Filtering, Database, RapidMiner, Graphical User Interface.